Comportamento mecânico sob fadiga de compósitos de polipropileno com reforço híbrido de fibras e microesferas ocas de vidro - Carvalho, Gustavo Baldi de (2018)
Short glass fiber (GF) reinforced polypropylene (PP) composites can be hybridized with hollow glass beads (HGB) in order to minimize the adverse effects arising from the preferential fiber orientation in injection molded parts, such as high mechanical properties anisotropy, differential shrinkage and warpage, and with additional advantage of reduced density of these ternary composites. These are important characteristics for engineering applications in lightweight and high-strength materials for the automotive, electro-electronic and home appliances industries. However, effective hybridization of a fibrous reinforcement with a particulate filler requires a clear understanding on the influence of interfacial interactions between the hybrid composite components (in this case, PP, GF and HGB, the last with and without silane treatment), on their mechanical properties. Thus, ternary composites of PP/GF/HGB with varying total and relative GF/HGB contents were prepared by dilution of pre-extruded concentrates of PP/GF and PP/HGB directly in the injection molding process and the short-term (tensile, flexural, impact and DMTA) and long-term mechanical properties (displacement controlled flexural fatigue) were analyzed. Tensile tests data of the ternary composites of PP/GF/HGB, in comparison to the binary composites of equivalent GF content, indicated an effective increase in the elastic modulus with increasing hybrid reinforcement content in the composites with up to 25 wt.% of GF. In the ternary composites with 30.0 wt.% GF, the elastic modulus tends to level off to the same modulus value of its corresponding binary composite of PP/30%GF, regardless of HGB content or its degree of interfacial adhesion with the PP matrix. However, the mechanical strength properties (tensile, flexural and impact) presented a strong dependence on the degree of polymer-HGB interfacial adhesion. In the hybrid composite systems with good PP-HGB adhesion, the strength values were equivalent to those of their corresponding binary PP/GF composites, whereas when PP-HGB adhesion is poor, the mechanical strength properties decreased slightly with increasing content of untreated HGB filler. Data from displacement-controlled three-point bending fatigue tests, monitored up to 106 cycles, showed differences between the fatigue stress amplitude decay rate behavior of the analyzed hybrid composites. Additionally, use of DMTA analysis in “as molded” and “post-fatigue” specimens revealed distinct behaviors due to different degree of interfacial interactions. The storage (E’) and loss (E”) modulus values indicated matrix polymer “strain softening” in the post-fatigue materials, while the mechanical damping tan δ curves were proportional to the energy dissipated by matrix-reinforcement interfacial frictional effects.